2022
DOI: 10.1093/ajhp/zxac064
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of FDA Table of Pharmacogenetic Associations and Clinical Pharmacogenetics Implementation Consortium guidelines

Abstract: Disclaimer In an effort to expedite the publication of articles, AJHP is posting manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…To identify inhibitors and inducers, the authors adopted the ‘List CYP inhibitors/inducers’ from the Food and Drug Administration (FDA) website [13]. In addition, the ‘Comparison of FDA Table of Pharmacogenetic Associations and Clinical Pharmacogenetics Implementation Consortium guidelines’ [14] was also examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify inhibitors and inducers, the authors adopted the ‘List CYP inhibitors/inducers’ from the Food and Drug Administration (FDA) website [13]. In addition, the ‘Comparison of FDA Table of Pharmacogenetic Associations and Clinical Pharmacogenetics Implementation Consortium guidelines’ [14] was also examined.…”
Section: Resultsmentioning
confidence: 99%
“…Table of Pharmacogenetic Associations and ClinicalPharmacogenetics Implementation Consortium guidelines'[14] was also examined.…”
mentioning
confidence: 99%
“…First, we used the RightMed Comprehensive Test Report categories of predicted drug‐gene interactions: none, minimal, moderate, and major drug‐gene interactions. Second, we integrated the widely accepted Clinical Pharmacogenetics Implementation Consortium (CPIC) guidelines for CYP2D6 and CYP2C19 , which infer the metabolizer phenotype from allelic variants of these genes, 22 with the widely used Flockhart Table 23 that provides a list of medications that are metabolized by cytochrome P450 enzymes (Figure 1). 24 CPIC guidelines categorize CYP2D6 and CYP2C19 metabolizer phenotypes as follows: ultrarapid metabolizer (UM), normal metabolizer (NM), intermediate metabolizer (IM), and poor metabolizer (PM).…”
Section: Methodsmentioning
confidence: 99%
“…113 Previous research has highlighted discrepancies and levels of concordance among the various consortia, regulatory agencies, and drug labels. 70,71 For example, an evaluation of 54 drugs known to have an actionable gene/drug interaction by CPIC guidelines found that only half had actionable information within the drug label. 71 Furthermore, only 18% of the drugs had agreement across regulatory agencies, including FDA and European Medicines Agencies.…”
Section: Drug Labelingmentioning
confidence: 99%